An Ion-Sensitive Field-Effect Transistor with Three-Dimensional Extended-Gate Architecture. (9th April 2019) - Teng, Nan-Yuan; Chen, Guan-Ying; Wang, Rui-Xing; Lin, Chih-Ting
Abstract : The ion-sensitive field-effect transistor (ISFET) is crucial to the field of chemical and biological sensing. Although ISFET with extended gate configuration is the current trend for application due to compatibility with standard CMOS process and convenience for array arrangement, the electric signal is attenuated significantly because an additional passivation capacitance is introduced, leading to a trade-off between pixel-resolution and sensitivity. Therefore, an ISFET array sensor with high pixel-resolution but at the same time with high sensitivity is a great desire. In this study, an attenuation-ameliorated extended gate-ISFET (EG-ISFET) with specially designed three-dimensional (3D) extended gate structure is proposed and realized based on the standard 0.35 μm CMOS technology. The transconductance of EG-ISFET is improved at most three times by the 3D structure as compared with the conventional EG-ISFET occupied the exactly same wafer area, achieving the goal of better sensitivity without sacrificing pixel-resolution.